2021
DOI: 10.1096/fj.202100293rr
|View full text |Cite
|
Sign up to set email alerts
|

Core circadian clock genes Per1 and Per2 regulate the rhythm in photoreceptor outer segment phagocytosis

Abstract: Retinal photoreceptors undergo daily renewal of their distal outer segments, a process indispensable for maintaining retinal health. Photoreceptor outer segment (POS) phagocytosis occurs as a daily peak, roughly about 1 hour after light onset. However, the underlying cellular and molecular mechanisms which initiate this process are still unknown. Here we show that, under constant darkness, mice deficient for core circadian clock genes (Per1 and Per2) lack a daily peak in POS phagocytosis. By qPCR analysis, we … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 73 publications
0
21
0
Order By: Relevance
“…This also holds biomedical significance as defective OSP may be part of the disease pathway in RAB28 ‐linked CRD and in other retinal and macular degenerations. Environmental cues are major regulators of OSP in other species with light‐dark transitions regulating OSP peaks in frog and Arvicanthis ansorgei , whereas internal circadian rhythms can drive OSP peaks in rat and mouse models 46,52,55 . In zebrafish, we observed a significant decrease in the number of RPE phagosomes present in the retinae of animals reared under a dark‐dark environment for <24 h (Figure 5), suggesting that the burst of OSP in zebrafish is not under circadian regulation.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…This also holds biomedical significance as defective OSP may be part of the disease pathway in RAB28 ‐linked CRD and in other retinal and macular degenerations. Environmental cues are major regulators of OSP in other species with light‐dark transitions regulating OSP peaks in frog and Arvicanthis ansorgei , whereas internal circadian rhythms can drive OSP peaks in rat and mouse models 46,52,55 . In zebrafish, we observed a significant decrease in the number of RPE phagosomes present in the retinae of animals reared under a dark‐dark environment for <24 h (Figure 5), suggesting that the burst of OSP in zebrafish is not under circadian regulation.…”
Section: Discussionmentioning
confidence: 93%
“…Significant progress has been made in identifying factors that mediate phagocytosis of rod OS in the RPE 53‐55 . However, our understanding of the factors (e.g., in photoreceptors) that initiate OSP is limited, as is whether OSP is regulated by the same factors at dawn and dusk peaks.…”
Section: Resultsmentioning
confidence: 99%
“…Although several studies have investigated the effects of clock genes removal in the retina, only two investigations have examined the effect of clock gene removal on the circadian regulation of phagocytic activity. In the first study, Per1/Per2 global KO blunted the peak in phagocytic activity, and 57 genes involved in photoreceptor phagocytosis were downregulated in the RPE [ 41 ]. In the second study, DeVera et al [ 42 ] developed an RPE-specific Bmal1 KO mouse model.…”
Section: Regulation Of Rpe Function In Vivomentioning
confidence: 99%
“…Thus, H1 receptor signaling is probably more dominant in mediating RPE circadian phase-shifts in h RPE cells [ 89 ]. Interestingly, another research group showed that three hours of a co-incubation with POS induced lysosomal marker, LAMP1, expression in cultured ARPE19 cells in a time-dependent manner [ 41 ]. Hence, this study indicates that the circadian clock regulates the phagocytic activity of the RPE, and photoreceptor outer binding availability and perhaps the phagocytic activity itself may provide feedback to the circadian clock in the RPE.…”
Section: Entrainment Of the Rpe Circadian Clockmentioning
confidence: 99%
“…The a-wave is determined notably by the magnitude of phototransduction (Li et al, 2018) and ionic currents at the level of photoreceptors (Robson & Frishman, 2014). We previously reported that the circadian clock regulates genes related to neurotransmission, ion channel activity and visual perception in mouse photoreceptors (Felder-Schmittbuhl et al, 2017;Bagchi et al, 2020;Milicevic et al, 2021). For instance, mRNA expression of several genes of the phototransduction cascade in rods (Pde6b, Cnga1, Sag, Rcvrn encoding subunits of the phosphodiesterase and of the cGMP-gated cation channel, the arrestin and recoverin) as well as of a number of ion channels vary along with the 24 h cycle in isolated photoreptors (Milicevic et al, 2021).…”
mentioning
confidence: 99%